Konsep Keseimbangan dalam Wayang Tauhid Lakon “Wedhare Sadat Tembayat” Sajian Ki Sunardi Wirocarito - Luwiyanto; M. Mukhtasar Syamsuddin; Lasiyo (Kawruh: Journal of Language Education, Literature and Local Culture, 2024)
Wayang tauhid is a new wayang creation created by Ki Sunardi Wirocarito from Trucuk Klaten since 1984. This wayang is a type of wayang dakwah that contains the story of the struggle of the walisanga to spread Islam in Java. There has not been much research done on this wayang tauhid by experts. One of its popular plays is ‘Wedhare Sadat Tembayat (WST)’. The text of this play is full of ethical values conveyed by the puppeteer. The purpose of this study is to find the answer to the question, what is the purpose of Javanese life implied in the wayang tauhid play WST. This philosophical research can be categorised as qualitative research by taking a literature study model. The research method used is hermeneutic with philosophical methodical steps. The results of this study can be formulated that the achievement of the Javanese goal of life is characterised by the perfection of a balanced relationship with God, a balanced relationship with fellow humans, a balanced relationship with non-humans (being the other), and a balanced relationship with the surrounding nature.